EDTA-assisted leaching of Pb and Cd from contaminated soil. (January 2017) - Qiao, Jiangbo; Sun, Huimin; Luo, Xiuhua; Zhang, Wang; Mathews, Shiny; Yin, Xianqiang
Abstract: Lead (Pb) and cadmium (Cd) contamination of soil and its harmful effects on human and environmental health have been one concern. In this study, batch and column leaching experiments were conducted to investigate the effects of two EDTA-assisted leaching methods, continuous and intermittent (dry-wet alternate), on the removal of Pb and Cd from contaminated soil. Total content and fractions of Pb and Cd at every 1 cm soil column depth were analyzed before and after the leaching. The results indicated that continuous leaching removed 75.43% of Pb (19.370 mg) and 53.21% of Cd (6.168 mg) and intermittent leaching removed 78.08% of Pb (20.051 mg) and 57.37% of Cd (6.650 mg), which showed intermittent leaching removed more Pb and Cd, but didn't differ significantly (P > 0.05) compared to the continuous leaching. In both leaching methods, total Pb and Cd content in all soil depths reduced after leaching. The two leaching methods made no significant differences in Pb and Cd distributions at different depths of the soil column. Highlights: Remediation of Pb and Cd contaminated soils with leaching methods is reported. Intermittent leaching had a better effect than continuous leaching. Pb showed higher removal efficiency than Cd in soil column. Cd was desorbed easier than Pb in soil column.